So close and yet so different: The importance of considering temporal dynamics to understand habitat selection - Richter, Laura; Balkenhol, Niko; Raab, Christoph; Reinecke, Horst; Meißner, Marcus; Herzog, Sven; Isselstein, Johannes; Signer, Johannes (Basic and applied ecology, 2020)
Habitat selection of animals is influenced by spatial heterogeneity as well as temporal environmental dynamics. In addition, human activities potentially have severe influences on the habitat selection of animals, often resulting in more nocturnal behavior. We investigated seasonal and circadian habitat selection patterns of red deer (Cervus elaphus) on a military training area in Bavaria (Germany). Individual deer ranged on two neighboring, but non-overlapping sites differing in landscape composition and human activity. Using GPS telemetry data, we visually investigated selection patterns and then fitted step-selection functions to assess multiple approaches to account for temporal (i.e., diel and seasonal) effects and for the impact of habitat conditions on selection. We first showed that the way in which time of day is considered in step-selection functions is essential for obtaining ecologically meaningful results, and that the usual ways of including time (i.e., either based on clock-time or based on night vs. day categories) can lead to incomplete or misleading conclusions. Furthermore, we found that individuals followed either circadian or seasonal habitat selection patterns, depending on the site they inhabited. This can be explained by differences in disturbance between the two sites. Except in winter, individuals selected for open habitats during the night irrespective of human activity level, but only individuals from the more disturbed site selected for covered habitats during the day. Our results highlight the importance of carefully considering the appropriate temporal scale for habitat selection analyses. Our findings also indicate that red deer are not a crepuscular or nocturnal species per se, as is often observed in human-dominated landscapes. Instead, our results imply that nocturnality in red deer is an effect of adaption to human activities.